The Darling - López, Lorraine, 1956- (Book collections on Project MUSE., 2015)
"A reinscription of Chekhov's short story 'The Darling' and set in Los Angeles in the 1970s through the present, the book tells the story of a young Latina who falls out of love again and again, with much help from Chekhov, Flaubert, Dreiser, Lawrence, Nabokov, and other deceased white men of letters"--